THE PRESENCE OF ROME IN THE EAST: IUDAEA CAPTA AND THE CULTURAL TRADITIONS OF THE ROMAN PALAESTINA - Teixeira-Bastos, Marcio [UNESP]; Abreu Funari, Pedro Paulo (Imprensa Univ Coimbra, 2019)
This paper analyzes Roman imperialist occupation in the Ancient East, the consequent domination of the Iudea and its transformation in Syria Palaestina. It addresses the demography and landscape of the region with the objective of demonstrating the intersection of external forces and internal forces that defined the fields of action in this interrelationship. It argues that proper Roman imperial administration, the organization of a network of orderly roads and an efficient traffic system allowed both military mobility and the formation of strategies for supplying, communicating and controlling the region by the population. It emphasizes categories of analysis, such as power, hegemony, domination, and resistance, stating that the formation of spaces is inherent in the understanding of the concept of space, the sphere of simultaneity, co-forming the social and power relations. States that the category of negotiation, in this sense, is what fosters spaces, feeds material practices, subsidizes identities, produces and mediates power. Finally, this paper points out to the importance of social contextuality, of archaeological contexts and of the contexts of discourse production, to approaches that privilege the perception of the different ideological conditions and contradictions inherent in social and material interactions in contact.
Keywords: Iudea Capta; Syria Palestina; Classical Archaeology